2020
DOI: 10.1186/s12933-020-01017-4
|View full text |Cite
|
Sign up to set email alerts
|

Change in glucose intolerance status and risk of incident cardiovascular disease: Tehran Lipid and Glucose Study

Abstract: Background: To assess the impact of changes in different glucose tolerance states on risk of incident cardiovascular disease (CVD)/coronary heart disease (CHD). Methods: A total of 4094 Iranians (43.9% men) aged ≥ 30 years, without diabetes and CVD at enrolment were included. The following categories were defined both at baseline visit and 3 years later (second visit): normal fasting glucose (NFG), normal glucose tolerance (NGT), NFG and NGT (NFG/NGT), impaired fasting glucose (IFG), impaired glucose tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…Collected data were then evaluated by a consulting committee, the outcome committee, included a principal investigator, an internist, an endocrinologist, a cardiologist, an epidemiologist, and the physician that collected the outcome data. Every confirmed event was considered as a NCD outcome based on ICD-10 criteria [8,15]. In this study, CHD was selected from ICD-10 rubric I20-I25.…”
Section: Definition Of Chdmentioning
confidence: 99%
“…Collected data were then evaluated by a consulting committee, the outcome committee, included a principal investigator, an internist, an endocrinologist, a cardiologist, an epidemiologist, and the physician that collected the outcome data. Every confirmed event was considered as a NCD outcome based on ICD-10 criteria [8,15]. In this study, CHD was selected from ICD-10 rubric I20-I25.…”
Section: Definition Of Chdmentioning
confidence: 99%
“…Collected data were evaluated by a consulting committee, the outcome committee, included a principal investigator, an internist, an endocrinologist, a cardiologist, an epidemiologist, and the physician who collected the outcome data and speci c outcomes. Every con rmed event was considered as a non-communicable disease outcome based on ICD-10 criteria [11,14]. In this study, CHD was selected from ICD-10 rubric I20-I25.…”
Section: De Nition Of Chdmentioning
confidence: 99%
“…In this study, CHD was selected from ICD-10 rubric I20-I25. CHD cases included [14][15][16][17]: (2) Cardiac procedure, de ned as a) angiography proven CHD with a result of ≥ 50% stenosis in at least one major coronary vessel, b) history of angioplasty or bypass surgery.…”
Section: De Nition Of Chdmentioning
confidence: 99%
“…Importantly, among general population, we have recently shown that the significant risk of IFG for CVD events was attributable to those population who converted from IFG state to diabetes. [33] Unfortunately, in the current study, we did not have adequate power to check this possibility in a cohort of subjects with history of previous CVD.…”
Section: Discussionmentioning
confidence: 85%